2006
DOI: 10.1007/s00134-006-0461-6
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of HemoCue in patients with gastrointestinal bleeding

Abstract: Although we demonstrated a low bias between HemoCue and blood hemoglobin determination, large HemoCue vs. hemoglobin differences may still occur, and therefore therapeutic decisions based upon capillary HemoCue alone should be very cautious.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 11 publications
2
24
1
2
Order By: Relevance
“…There has been some investigation of the accuracy of HemoCue® to measure Hb in some clinical disease states, e.g. gastrointestinal bleeding [27] and as a screening tool for blood donations [28][29][30], however to our knowledge there has been no exploration of whether HemoCue® is as accurate as the gold standard hematology analyzer for measuring Hb in individuals with genetic Hb disorders.…”
Section: Introductionmentioning
confidence: 99%
“…There has been some investigation of the accuracy of HemoCue® to measure Hb in some clinical disease states, e.g. gastrointestinal bleeding [27] and as a screening tool for blood donations [28][29][30], however to our knowledge there has been no exploration of whether HemoCue® is as accurate as the gold standard hematology analyzer for measuring Hb in individuals with genetic Hb disorders.…”
Section: Introductionmentioning
confidence: 99%
“…In patients admitted to ICUs for gastrointestinal bleeding, Van de Louw et al reported a low mean difference (bias, 0.06 ± 0.87 g/dl) between hemoglobin level determined by a laboratory and that of capillary blood samples. 6 These authors found that 21% of the differences were greater than 1 g/dl. Rippmann et al observed a bias of 0.6 ± 0.6 g/dl between hemoglobin levels determined by a central laboratory and those from a HemoCue ® system for capillary blood.…”
Section: Hemoglobin Measurement By Occlusion Spectroscopymentioning
confidence: 99%
“…Although most authors have defined inaccurate measurement as an absolute difference (i.e., >1 g/dl) and have excluded patients from their analysis in whom measurement of hemoglobin level by a device was technically unavailable, 13,17 the proportion of inaccurate measurements that we found appears to be consistent with previous studies. 6,13,14,18 For the occlusion spectroscopy-based method, the proportion of inaccurate measurements appears to be clinically unacceptable and is globally comparable to the oximetrybased method. 14,18 Despite significant correlations with the reference method for both SoHb and cHb, the BlandAltman method suggests that the bias, precision, and limits of agreement for SoHb cannot substitute for the reference method.…”
Section: Hemoglobin Measurement By Occlusion Spectroscopymentioning
confidence: 99%
See 2 more Smart Citations